2007
DOI: 10.1111/j.1444-2906.2007.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Recording cerebellar neuron activities in swimming goldfish

Abstract: Neuronal activities were investigated in the cerebellum of immobilized and swimming goldfish Carassius auratus. Extracellularly recorded neural activities of the cerebellum in immobilized goldfish were characterized and classified into five types. Based on the waveforms and recording depths, these five neural activity types were estimated to originate from three identified classes of cerebellar neurons: Purkinje cells, eurydendroid cells, and granule cells. Chronic recording of cerebellar neuron activities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Since it is not known which subdivisions of the corpus cerebelli are involved in classical fear conditioning, the recording site locations were reported as follows: 1) rostral and ipsilateral to the CS-presented side; 2) rostral and contralateral to the CS-presented side; 3) caudal and ipsilateral to the CS-presented side; and 4) caudal and contralateral to the CS-presented side. PCs were identified according to previous studies on the basis of types of action potentials (simple or complex spikes) and the depths (500–800 μm) of the recording positions [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is not known which subdivisions of the corpus cerebelli are involved in classical fear conditioning, the recording site locations were reported as follows: 1) rostral and ipsilateral to the CS-presented side; 2) rostral and contralateral to the CS-presented side; 3) caudal and ipsilateral to the CS-presented side; and 4) caudal and contralateral to the CS-presented side. PCs were identified according to previous studies on the basis of types of action potentials (simple or complex spikes) and the depths (500–800 μm) of the recording positions [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In goldfish, firing frequencies of the complex spikes were low (usually less than 1 Hz) [ 25 ] and artifacts due to the electric shock US were considerably large. This situation prevented us with accurate peristimulus analysis of complex spike firings in some cases.…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiological studies revealed that some sensory stimuli evoked action potentials in cerebellar neurons of the goldfish (Kotchabhakdi 1976) and the catfish (Lee and Bullock 1984). Recently recordings of neuronal activities could be succeeded from swimming goldfish (Matsumoto et al 2007b).…”
Section: Functions Of Teleost Cerebellummentioning
confidence: 99%